Alfalfa Haylage Production in Central and Eastern Kansas - Warmann, Gerald W.; Fausett, Marvin R. (My University, 1997)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa haylage production in central and eastern Kansas.
MF523_1997_10
Keywords: MF523; Economics; Crops; MF